World music traditions and transformations - Bakan, Michael B.; Senungetuk, Heidi; Shonekan, Stephanie (McGraw Hill, 2024)
World Music: Traditions and Transformations, fourth edition, is an introductory-level survey of diverse musics from around the world. It assumes no prior formal training or education in music, and with one brief exception avoids the use of Western music notation entirely. It is written primarily for undergraduate nonmusic majors but is equally appropriate for music majors, and is therefore ideal for courses enrolling music and nonmusic stu-dents alike"--